CSR and management accounting challenges in a time of global crises - Oncioiu, Ionica, 1972- (Advances in finance, accounting, and economics (AFAE) book series., 2021)
"This book presents an interdisciplinary perspective of the various theoretical and practical approaches of management accounting and its impact in the 21st century on different areas of activity, including sustainable performance faced by the current business environment, and in particular management corporations"--